Effectiveness of Netarsudil as an Additional Therapy for Glaucoma in Patients Already on Maximally Tolerated Medical Therapy - Villegas NC (Dove Medical Press, 2021)
Natacha C Villegas, Wen-Shin Lee Department of Ophthalmology, Stanford University School of Medicine, Stanford, CA, USACorrespondence: Natacha C VillegasDepartment of Ophthalmology, Stanford University, Medical Center, 2452 Watson Court, Palo Alto, CA, 94303-5353, USATel +1 832 477-3498Email natachav@stanford.eduPurpose: This study seeks to evaluate the effectiveness of netarsudil (Rhopressa) in patients with inadequately controlled IOP on otherwise maximally tolerated medical therapy.Methods: This is a retrospective study of patients started on netarsudil at Stanford University. Exclusion criteria included glaucoma surgery or laser within 6 months of starting netarsudil and other modifications to the baseline medication regimen within 4 weeks of starting netarsudil. The primary outcome was treatment success, defined as IOP reduction meeting a predetermined target, and no further medication, laser, or surgery recommended subsequent to starting netarsudil.Results: Sixty-two eyes were included, and 36 (58%) achieved treatment success at first follow-up. Mean baseline IOP was 19.5 ± 5.6 mmHg on a mean of 3.5 ± 0.7 ocular hypotensive medications. The mean change in IOP from baseline to first follow-up was − 3.53 mmHg (− 17%). In patients who achieved treatment success, mean IOP change was − 5.22 mmHg (− 28.0%). Of the eyes with baseline IOP ≤ 20 mmHg, 69% achieved treatment success, compared to only 17% of eyes with baseline IOP ≥ 21 mmHg (P < 0.05).Conclusion: Netarsudil is effective in lowering IOP for patients on otherwise maximally tolerated medical therapy, for which glaucoma laser or surgery would have been the only remaining therapeutic options. Treatment success was more likely in eyes with baseline IOP under 20 mmHg.Keywords: netarsudil, Rhopressa, maximally tolerated medical therapy, glaucoma